Actitudes ambientales de la población en el asentamiento humano Masusa en el distrito de Punchana, Maynas 2021 - Pezo Peña, Gianela del Pilar (2023)
The objective of this work was to describe the environmental attitudes in the inhabitants of the Masusa human settlement in the year 2021. Due to its approach, it was quantitative, prospective, simple descriptive and non-experimental in design. The target population was 1,056 inhabitants, with a minimum of two years of experience and with housing in the place. The sample was also made up of 105 residents, inclusion and exclusion criteria were taken into account, the technique was the survey and the instrument applied was a questionnaire of ten positive and negative statements, the same one that passed the validity tests (valid index of Aiken ) and reliability (Cronbach 's alpha test ). The data were analyzed taking into account the objectives and the hypothesis and analyzed, processed and tabulated through the statistical package SPSS version 23. The results expressed that 30.5% and 21.5% of the surveyed inhabitants showed an unfavorable and neutral general environmental attitude compared to the favorable attitude that obtained 30.5% and that is found in equal proportion to the favorable and very favorable both in males and females. The unfavorable and neutral environmental attitude is found in a lower proportion than the favorable and very favorable in the level of instruction without studies, but in greater proportion in the primary and secondary levels of instruction. It is recommended to strengthen in a general way the favorable and very favorable general attitudes towards environmental conservation in the inhabitants of the human settlement Masusa , through the active participation of the regional and provincial institutions in charge of this purpose as well as developing awareness work on the importance of conservation. environmental conservation in the inhabitants of said human settlement, especially in the sector of inhabitants with a higher degree of education.